Risk and protective factors for mental health and wellbeing in childhood and adolescence - Anne Nolan; Emer Smyth (The Economic and Social Research Institute (ESRI), 2021)
ESRI research funded by HSE Health and Wellbeing, examines the risk and protective factors for mental health and wellbeing of children and young people. Using data from the Growing Up in Ireland '08 Cohort at 9 years of age and the '98 Cohort at 17 years of age, the research examined both positive (life satisfaction) and negative (socio-emotional difficulties) aspects of mental health and wellbeing. Socio-emotional difficulties refer to difficulties of an emotional nature (e.g., feeling unhappy, downhearted or tearful) or with peers (e.g., picked on or bullied).
Keywords: 330